Study on 5G networking scheme - Qing LI (Dianxin kexue)
5G network architecture,network characteristics and network deployment requirements of 5G typical services were mainly described.At the same time,5G core network,5G bearer network,5G access network end-to-end networking scheme suggestions were put forward,and 5G signaling network organization and routing mode in multiple scenarios were proposed,in order to provide reference for speeding up the commercial deployment of 5G network for telecom operators.